2023
DOI: 10.1186/s40168-022-01457-y
|View full text |Cite|
|
Sign up to set email alerts
|

Genes mcr improve the intestinal fitness of pathogenic E. coli and balance their lifestyle to commensalism

Abstract: Background The plasmid-mediated resistance gene mcr-1 confers colistin resistance in Escherichia coli and paves the way for the evolution to pan-drug resistance. We investigated the impact of mcr-1 in gut colonization in the absence of antibiotics using isogenic E. coli strains transformed with a plasmid encoding or devoid of mcr-1. Results In gnotobiotic and conventional mice, mcr-1 significantly enhanced intestinal anchoring of E. coli but impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…The significance of these mutations for bacterial association with flies, however, has not been tested. E. coli strain that is made resistant to AMPs by mcr-1 gene expression similarly showed better ability to persist in the mouse gut, highlighting an important role of AMP resistance for commensal lifestyle [72].…”
Section: Discussionmentioning
confidence: 99%
“…The significance of these mutations for bacterial association with flies, however, has not been tested. E. coli strain that is made resistant to AMPs by mcr-1 gene expression similarly showed better ability to persist in the mouse gut, highlighting an important role of AMP resistance for commensal lifestyle [72].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Gram-negative bacteria are notorious for their capacity to develop resistance due to their intrinsic resistance. Thus, naturally occurring genes such as RND superfamily genes [8] or mcr [17] can increase the fitness of a strain as well as its resistance to antimicrobials. To shed light on the potential of microcins as new therapies and subsequently any potential cross-resistance, a previous study was conducted [18].…”
Section: Introductionmentioning
confidence: 99%
“…H&E staining images clearly reflected the intact and orderly skin structures in the PNS@CMCS, BSP-CMCS, and BSP-PNS@CMCS groups, in remarkable contrast to the incomplete epidermis in the Ctrl and CMCS groups (Figure a). The epidermal thickness of the newly generated skin is usually used as one of the criteria for wound healing. , It was found that PNS@CMCS (59.36 ± 20.10 μm), BSP-CMCS (62.40 ± 14.96 μm), and BSP-PNS@CMCS (85.50 ± 23.43 μm) groups had significantly thicker epidermis than the Ctrl (35.10 ± 13.27 μm) and CMCS (41.65 ± 13.11 μm) groups (Figure b). Meanwhile, fewer inflammatory cells and more skin appendages could be observed in the newly generated skin tissue of BSP-PNS@CMCS group as compared to other groups, suggesting that the enhanced functional reconstruction of wound tissues by BSP-PNS@CMCS dressings.…”
mentioning
confidence: 96%
“…Cutaneous wounds may be infected when they are in contact with these contaminated sources. By contrast, S. aureus colonizes frequently in other sites such as the skin, throat, axillae, groin and intestine, or persistently in a tiny proportion of human’s nose. Notably, the hypodermis is the predominant site for S. aureus infections to cause cellulitis. After epidermal damage, the dysbiosis of normal microbial community will increase the risk of overgrowth of harmful pathobionts including the S. aureus infection.…”
mentioning
confidence: 99%